PERILAKU KAWIN, UJI RESPON DAN IDENTIFIKASI SPESIES LALAT BUAH PADA BELIMBING, KETAPANG, DAN PARIA - Dumalang, Sherlij; Lengkong, Maxi (Universitas Sam Ratulangi, 2011)
ABSTRACT Fruit flies is one of the important pests which attack fruits in Indonesia and very detrimental economicaly. The objective of this research was to determine mating behaviour of fruit flies Bactrocera sp., testing their response to attractants methyl eugenol and cue lure as well as identification some species of fruit flies that attack belimbing, ketapang and paria fruits. The fruits samples which were affected by fruit flies were collected from plantation at Lopana and Kapitu, South Minahasa. Imago was assessed at laboratory of entomology, Faculty of Agriculture. Result showed that mating time of these species was occured between 17.10 – 18.45. Sexual maturity of belimbing fruit flies was 10 -12 days. Whereas ketapang fruit flies and paria fruit flies were 10 – 14 days and 11 – 13 days respectively. B. dorsalis complex was attracted to methyl eugenol. While B. albistrigata and B. cucurbitaceae Coq.were attracted to cue lure. Keywords : fruit flies Bactrocera sp. Belimbing, ketapang, paria fruits, methyl eugenol and cue lure